Probus : International Journal of Romance Linguistics (De Gruyter Mouton, 1989)
Probus is a platform for the discussion of historical and synchronic research in the field of Latin and Romance linguistics, with special emphasis on phonology, morphology, syntax, language acquisition and sociolinguistics. The journal encourages problem-oriented contributions that combine the solid empirical foundations of philological and linguistic work with the insights provided by modern theoretical approaches.